TEACHING ENGLISH LANGUAGE READING SKILLS TO STUDENTS OF HIGHER EDUCATION PILOT PROJECT - Kadirova Firuza Rustamovna (Galaxy International Interdisciplinary Research Journal, 2021)
The present paper will present the results of my pilot project, which is a part of my larger doctoral work. The project involves identifying the needs of 32 students in the experimental group and 31in the control group from among the first year students of English specialty at the Samarkand State University in Samarkand, Uzbekistan, for the improvement of their reading skill. The current level of reading proficiency of both the groups was identified through a diagnostic test. Subsequently, students in the experimental group were trained for a semester through a specially prepared interactive manual. After the semester, the students of both the groups were again tested for their reading proficiency. The aim is to find out whether students, when consciously trained for reading, do improve their reading skills in contrast to the students trained in the traditional way. The paper highlights some important strategies that are necessary for the improvement of reading skills.